Classification of Septic Shock Phenotypes Based on the Presence of Hypotension and Hyperlactatemia in Cats - Troia, Roberta; Buzzurra, Francesca; Ciuffoli, Elena; Mascalzoni, Giulia; Foglia, Armando; Magagnoli, Ilaria; Dondi, Francesco; Giunti, Massimo (Frontiers in Veterinary Science, 2021)
Background: Three different phenotypes of septic shock based on changes in blood pressure and lactate are recognized in people. Dysoxic shock, representing the combination of fluid-refractory hypotension and hyperlactatemia, is characterized by greater disease severity and mortality compared to cryptic shock (hyperlactatemia alone) and vasoplegic shock (hypotension with normal blood lactate). Little is known about septic shock and specifically its phenotypes in cats. Objective: To analyze the characteristics and prognostic implications of three septic shock phenotypes in cats with sepsis. Methods: Cats with septic shock were prospectively included. Septic shock was defined by the presence of hypotension (mean blood pressure <60 mmHg) requiring vasopressor support and/or persistent hyperlactatemia (>4 mmol/L) and classified in three subgroups: dysoxic shock, vasoplegic shock and cryptic shock. Clinical and clinicopathological variables including APPLEfast and APPLEfull scores, occurrence of multi-organ dysfunction syndrome (MODS; presence of at least two dysfunctional organs simultaneously) and outcome were compared among subgroups. Cats with sepsis showing normal blood pressure and lactate concentrations hospitalized during the study period were included as uncomplicated sepsis, and compared to cats with septic shock for selected variables. Length of hospital stay and mortality were evaluated in the whole study population. Odds ratios for mortality were calculated using logistic regression analysis. Significance was set at P < 0.05. Results: The study enrolled 48 cats with uncomplicated sepsis and 37 cats with septic shock (dysoxic shock n=17; vasoplegic shock n=11; cryptic shock n=7). Cats with dysoxic shock had significantly higher APPLEfast and APPLEfull scores compared to vasoplegic and cryptic shock. Mortality rates were not significantly different among cryptic (57%), dysoxic (65%) and vasoplegic shock (91%), while MODS occurrence was significantly lower in cats with cryptic shock (57%) compared to patients affected by dysoxic (94%) and vasoplegic (100%) shock. Cats with septic shock had higher frequency of MODS and greater mortality rate than cats with uncomplicated sepsis. Conclusion: Despite similar in-hospital mortality, cats with dysoxic and vasoplegic shock are characterized by having higher occurrence of multi- organ dysfunction compared to cats affected by cryptic shock. Results from this study suggest novel means of identifying high-risk subgroups of septic cats